KEPUASAN KERJA MEMEDIASI MOTIVASI DAN KECEDASAN EMOSIONAL TERHADAP KINERJA DOSEN PNS Dpk DAN DOSEN YAYASAN PADA KOPERTIS WILAYAH XI KALIMANTAN (STUDI PADA FE UVAYA, FE UNISKA DAN STIMI BANJARMASIN) - Abdul Wahab; Mahfuzil Anwar; Arfie Yasrie (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2018)
Abstract, Individuals involved in the organization have many aspects that can contribute to the achievement of organizational goals that include different knowledge, experience, skills, personality, feelings and will and create those behaviors, which human behavior is learned in work environment and in carrying out their job duties. Humans are also studied in their interactions with their work, with their physical work environment, and with the social environment of their work which is a reciprocal and influencing relationship. However, employees are not always successful in acting out their role without causing trouble. This phenomenon can occur because employee issues can be caused by the situation and condition of the company or organization or institution. Conversely, corporate or institutional problems can also be caused by human behavior itself. Similarly, strengths, weaknesses and other things that exist in employees is a potential that will affect the performance. It is not only intellectually in terms of cognitive or control of the task (skill), but also the emotional intelligence that can affect its performance. Emotional Intelligence is an emotional skill that enables the individual to develop his emotional self-control, has courage and persistence, is able to show empathy so that he / she is able to relate to others well, as they will produce outstanding performance in the work.